Analisis Pengaruh Earning Per Share, Return On Equity, dan Debt To Equity terhadap Harga Saham Property dan Real Estate Tahun 2015-2018 - Elsa Firlyani; Ali Alexader (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research aims to investigate the impact of Return on Equity (ROE), Debt to Equity Ratio (DER), and Earning Per Share (EPS) on stock prices in the Property and Real Estate sector in Indonesia during the period 2015-2018. The analysis employs a panel data model approach, including three regression models: Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Chow Test, Hausman Test, and Lagrange Multiplier Test are utilized to select the most suitable model, while classical assumption tests are conducted according to the estimation method. The findings indicate that EPS significantly influences stock prices positively, while ROE and DER do not show a collectively significant impact. The research conclusion underscores the dominant role of EPS in shaping stock price movements in this sector, providing crucial insights for the financial management of Property and Real Estate companies.